2021
DOI: 10.1002/mnfr.202100650
|View full text |Cite
|
Sign up to set email alerts
|

β‐Carotene Bioavailability and Conversion Efficiency Are Significantly Affected by Sex in Rats

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 57 publications
2
21
0
Order By: Relevance
“…The fact that plasma retinol concentrations were not significantly different between the C+, SP and BSFL groups was not very surprising. Indeed, there was VA or proVA in the diet of all these groups and it is well established that serum retinol is very well regulated and only begins to decline when hepatic VA stores are nearly depleted (Borel et al, 2021b). Thus the fact that plasma retinol concentrations were not significantly lower in the C-group, as compared to the other groups, simply shows that this group was not deficient enough to affect hepatic retinol secretion and hence retinolemia (Borel et al, 2022;Borel et al, 2021b).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The fact that plasma retinol concentrations were not significantly different between the C+, SP and BSFL groups was not very surprising. Indeed, there was VA or proVA in the diet of all these groups and it is well established that serum retinol is very well regulated and only begins to decline when hepatic VA stores are nearly depleted (Borel et al, 2021b). Thus the fact that plasma retinol concentrations were not significantly lower in the C-group, as compared to the other groups, simply shows that this group was not deficient enough to affect hepatic retinol secretion and hence retinolemia (Borel et al, 2022;Borel et al, 2021b).…”
Section: Discussionmentioning
confidence: 96%
“…The measurement of retinol, retinyl-ester and β-C concentrations in the blood and the liver, which is by far the main storage organ for VA , gives both an indication of the quantity of VA, or proVA, which was absorbed from the diets, but it also gives a precise indication of the VA status of the animals, the concentration of VA in the liver being considered as the best marker of the VA status . Finally, it gives an idea of the conversion rate of β-C in VA by calculating the β-C/(retinol + retinyl-esters + β-C) ratio when the only dietary source of VA is β-C (Borel et al, 2021b). The discussion will therefore consist in interpreting the data obtained in the plasma then in the liver and then in making a synthesis of these observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And men may tend to smoke a lot and drink more alcohol from social activities than women. These lifestyle habits may raise the body's active oxygen, and as a result, more active oxygen radicals accumulates in the body, which is thought to have a greater effect on the blood concentration of vitamin A than women 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Lemke et al observed a decrease in β-carotene conversion efficiency following VA supplementation together with an increase in the absorption of β-carotene [22] while Goswami et al [10] observed a decrease in β-carotene bioavailability in case of VA deficiency. We therefore decided to reinvestigate this regulation in a recent study which aimed to assess the effect of dietary VA content on intestinal and hepatic metabolism of VA in adult rats [24]. The results of this study first allowed us to hypothesize that this regulatory mechanism may only be effective when the VA status is very low.…”
Section: ) Introductionmentioning
confidence: 99%